2018
DOI: 10.3390/rs10091408
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Fetch Effect Using Onshore and Offshore Vertical LiDAR Devices

Abstract: An offshore wind measurement campaign using vertical light detection and ranging (LiDAR) devices was conducted at the Hazaki Oceanographic Research Station (HORS) as part of an investigation into determining the optimal distance from the coast for a nearshore wind farm from a meteorological perspective. The research platform was a 427 m long pier located on a rectilinear coastline on the Pacific coast of the central Honshu Island in Japan. The relationship between the ratios of the increase of wind speed near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 14 publications
(19 reference statements)
0
17
0
Order By: Relevance
“…The readers are referred to Barthelmie et al [12] for existing research and recommended practices for offshore wind speed measurements using in situ and remote sensing technologies. In this regard, Shimada et al [13] conducted a LiDAR-based measurement campaign in a coastline area to investigate changes in wind speed and turbulence level when the wind transitions from onshore to offshore wind or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…The readers are referred to Barthelmie et al [12] for existing research and recommended practices for offshore wind speed measurements using in situ and remote sensing technologies. In this regard, Shimada et al [13] conducted a LiDAR-based measurement campaign in a coastline area to investigate changes in wind speed and turbulence level when the wind transitions from onshore to offshore wind or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…As an attractive and applicable alternative to meteorological towers, Doppler LiDARs have been mounted on different platforms to measure wind speeds and directions over the sea. Shimada et al [110] used two ground-based LiDARs to investigate coastal wind modifications, known as the fetch effect, to determine the optimal distance from the coast for a nearshore wind farm. Their results indicated that the wind speed increased with the increase of the fetch length within 5 km of the coast.…”
Section: Wind Resource Assessmentmentioning
confidence: 99%
“…The winds offshore in the coastal zone were investigated using two vertical profiling pulsed lidars by Shimada et al [31]. The instruments were located at the coast and 400 m out, mounted on a long pier in Japan.…”
Section: Overview Of Contributionsmentioning
confidence: 99%